P-graph approach in value chain modeling of rice husk-fired biomass processes - Maleniza, Michael Reiji A. (Animo Repository, 2022)
The world energy demand will keep rising and put a strain on all sources of energy unless a change is made. Countries, like the Philippines, which rely heavily on agriculture can make use of the biomass they produce to generate energy. This paper developed a framework on rice husk-fired biomass value chains using P-graph which generate high-value energy products. A process flow diagram was first created using existing literature to determine the input flows and output flows between each technology to be used for the conversion of rice husks into high-value energy products. This process flow diagram was then transformed into a P-graph model. Two case studies were created from this process flow diagram where the first one only generates bioelectricity as its high-value energy product while the second one generates diesel, jet fuel, and bioelectricity as its high-value energy products. An optimal solution structure was chosen from each case study based on its economic returns and environmental impact. A sensitivity analysis was performed on the optimal solutions of both case studies to determine the effect of changing the product demand on the overall system. The results of these case studies show that the framework can produce optimal solutions which generate high-value products at a steady profit and low environmental impact. The framework presented can be used to help guide policy decisions by transforming existing rice-based value chains to be more efficient and sustainable.